Parameter design of an ISG hybrid electric trackless rubber tyred vehicle based on degree of hybridisation. (2017) - Han, Peixin; Bao, Jiusheng; Ge, Shirong; Yin, Yan; Ma, Chi; Yang, Shuai
Present techniques on trackless rubber tyred vehicle (TRTV) driven by flameproof diesel engine and battery have serious problems such as environmental pollution and power shortage. Therefore, hybrid electric trackless rubber tyred vehicle (HETRTV) becomes an important development direction. This paper focuses on the relationship between the degree of hybridisation (DOH) and dynamic performance, fuel economy and cost, and a novel method is proposed to determine the optimal DOH. The dynamic performance and fuel consumption of the HETRTV were simulated by ADVISOR based on 4WD model and CYC_WCQ driving cycle, which were established by software secondary development. The results show that the optimal DOH is 0.33. Compared with WCQ-3B type TRTV, the equivalent fuel consumption of HETRTV is significantly reduced by 12.8%, which demonstrates that the application of hybrid technology in TRTVs is greatly beneficial for improving the fuel economy and underground working environment.